(untitled) (Journal of Parents and Teachers, 2014)
The author of this article proposes to make a formative trip to understand the current leisure of children and young people. In this symbolic universe, alcohol is one of the main protagonists. In the article, it is exposed causes, reflections, opinions of young people and of the own author on this subject.